VIOLENCE TOWARDS SAYURI IN ARTHUR GOLDEN’S MEMOIRS OF A GEISHA: A SOCIALIST FEMINISM APPROACH - Hani, Nurlita Puspa; Suyudi, Ichwan; Hawasi, Hawasi (Journal of Language and Literature, 2016)
Violence, an assault on a person’s control over her/his body and life, can take many forms and has varying consequences depending on the type of assault, its context and interpretation, the chronicity of violence, and availability of support. Feminist theory is becoming the dominant model for explaining violence towards women. The problems of this study are; what kinds of violence that happened towards Sayuri and what the reasons of violence that happened towards Sayuri from Socialist Feminism point of view are. The aims of this study are; to find out the kinds of violence that happened towards Sayuri and to find out the reasons of violence that happened towards Sayuri from Socialist Feminism point of view. This study used qualitative descriptive method in analyzing the data. Qualitative descriptive studies is a comprehensive summarization, in everyday terms, of specific events experienced by individuals of groups of individuals. After analyzing the data it can be concluded that Sayuri experienced four kinds of violence; physical violence, psychological violence, sexual violence, and economic violence and the reasons of violence that happened towards Sayuri from Socialist Feminism point of view are because of the difference of social class and economic status.Keywords: Sociolinguistics, Code Mixing, Types of Code Mixing, Alternation, Insertion, Congruent Lexicalization, The Reason of Using Code Mixing